2013
DOI: 10.5923/j.food.20120206.02
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of “Ricotta” Cheese Produced at Laboratory Level

Abstract: Ricotta cheese is made fro m heat-acid precipitation o f p rotein fro m whey or whey-milk blend. The study aimed to evaluate the quality characteristics of ricotta cheese produced at laboratory level. The chemical co mposition of ricotta cheese was as follows: mo isture: 72.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Melting point is an important physical characteristic of fat compounds, which is useful for their identification, and it is crucial in many technological applications of fats. The MP of fatty acids increases with increasing chain length and decreases with increasing degree of unsaturation (Sulieman et al, 2013). No significant difference was observed between the MP of buffalo and cow ghee.…”
Section: Composition and Physicochemical Characteristics Of Ghee Samplesmentioning
confidence: 76%
See 1 more Smart Citation
“…Melting point is an important physical characteristic of fat compounds, which is useful for their identification, and it is crucial in many technological applications of fats. The MP of fatty acids increases with increasing chain length and decreases with increasing degree of unsaturation (Sulieman et al, 2013). No significant difference was observed between the MP of buffalo and cow ghee.…”
Section: Composition and Physicochemical Characteristics Of Ghee Samplesmentioning
confidence: 76%
“…The result of the MP of buffalo and cow ghee was within the range of that reported by Bindal and Wadhwa (1993) (32.7-35.8 and 33.4-38.8°C for cow and buffalo ghee, respectively). While in the study of Sulieman et al (2013), the MP of three ghee purchased in local markets in Sudan and the ghee prepared in the laboratory was reported 37, 38, and 37°C, 37°C, respectively. The MP of ghee samples in their research is higher than those of the present study.…”
Section: Composition and Physicochemical Characteristics Of Ghee Samplesmentioning
confidence: 99%
“…Souza et al (33) evaluated 30 samples of Ricotta and found that 16.67% of the samples could be classified as low-fat cheese, 23.33% as semi-fat cheese and 60% as full-fat cheese. In the chemical composition of Ricotta cheese produced in laboratory conditions water was dominant (72.89%), while protein, fat and ash were amounted by only 0.6%, 0.7%, and 6.9%, respectively (34). Examining artisanal and industrial Ricotta samples Mattera et al (35) noticed that industrial Ricotta showed a greater homogeneity in view of their chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…Ricotta cheese were Sensory evaluated for appearance, texture, flavor and Overall Acceptability according to scheme described by Sulieman et al (2012).…”
Section: Sensory Evaluation Of Ricotta Cheesementioning
confidence: 99%